PERSEPSI MAHASISWA TERHADAP PEMANFAATAN PERPUSTAKAAN POLITEKNIK LP3I DALAM TRIDHARMA PERGURUAN TINGGI - Andi Setiawan (JURNAL LENTERA BISNIS, 2019)
The three pillars of higher education for lecturers and students is an obligation. The law requires the existence of libraries in universities for those who want to organize higher education. The library, which is a sub-section of the college where it belongs, must participate in the success of the main organization's missions. The presence of the library must provide tangible benefits for academic people. The Kramat LP3I business administration students as the main actors in this study fully participated to realize the goals of the institution. They have a positive impression of the existence of the library. The results showed that the  students' perceptions of the use of the Kramat LP3I Polytechnic library in the three pillars of higher education activities were approaching good either at 74.9%.Key words: Perception, Library, LP3I Polytechnic Students. The three pillars of higher education.